Leading with Emotional Intelligence Effective Change Implementation in Today's Complex Context - Higgs, Malcolm; Dulewicz, Victor (Springer International Publishing : Imprint: Palgrave Macmillan, 2016)
Drawing on research into leadership and emotional intelligence, this book presents a framework that can lead to effective change implementation. Set against a backdrop of increasing complexity, volatility and uncertainty, the book responds to the need for organisations to continuously change and transform, and addresses the real challenges of effective implementation. Exploring these concepts at individual, team and organizational levels, Leading with Emotional Intelligence recognises the complexity of the topic and combines rigour with relevance to underpin the framework with empirical evidence.